Pengaruh Shalat Lima Waktu terhadap Disiplin dan Kualitas Hidup - Muhammad Zainul Arifin; Ainur Rofiq Sofa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to investigate the effect of the five daily prayers on the discipline and quality of life of Muslim individuals. Prayer as one of the pillars of Islam has an important role not only in the spiritual aspect, but also in the development of character and daily lifestyle. The method used in this study is a mixed approach, namely qualitative and quantitative, involving 200 respondents who routinely perform prayers. Data were collected through questionnaires and in-depth interviews to understand the impact of prayer on personal discipline, mental health, and overall quality of life. The results showed that 85% of respondents felt an increase in discipline in managing time and responsibility after performing prayers regularly. In addition, 75% of respondents reported an increase in quality of life characterized by better mental health, reduced stress, and improved social relationships. These findings indicate that the practice of the five daily prayers not only contributes to the spiritual aspect, but also has a significant positive impact on the discipline and quality of life of individuals. This study is expected to be the basis for further research on the role of worship in improving the welfare of individuals and society.